Contribution of selected factors on farmers’ work performance towards fertilizer application in rice of Bangladesh - Bagum, Thahamina; Uddin, Md. Kamal; Hassan, Salim; Kamarulzaman, Nitty Hirawaty; Rahman, Md. Zulfikar; Haque, Ahmad Numery Ashfaqul (Multidisciplinary Digital Publishing Institute, 2021)
There is enormous possibility to increase rice yield in Bangladesh. Inefficient and often imbalanced fertilizer use impedes farmers from achieving expected yields. It is evident from past research that farmers have resorted to applying fertilizers at inappropriate rates that do not match well with the nutrient requirement of certain crops. Therefore, this study explores the contribution of selected factors that influence farmers’ work performance and determine the highest contributing factors on farmers’ work performance towards fertilizer application in rice. This research used a multistage simple random sampling method to select 355 farmers from twenty-one rice production areas of Bangladesh. Data, collected using a structured questionnaire, were subjected to multiple linear regression analysis to explore the contribution of selected factors and identify the highest contributing factors towards farmers’ work performance. Results revealed that all the factors explained 56.1% of the variance in farmers’ work performance. Motivation of farmers was found to be the highest contributing factor, followed by knowledge that influences farmers’ work performance. The study concludes that farmers need to be equipped with essential knowledge and motivation crucial to strengthening their work performance as this will subsequently increase rice production.